2017
DOI: 10.1007/s10033-017-0161-x
|View full text |Cite
|
Sign up to set email alerts
|

Designing Visceral, Behavioural and Reflective Products

Abstract: Designers and manufacturers often see consumption as the primary objective of a product -with implications such as discarded products, obsolete wastes, and ecological degradation. The paper aims to find the answer to the question, how emotional design can adapt the discarded and undesirable products into something valuable in a long term? This paper presents a framework combining Chapman's theory and Norman's theory on three levels of emotional design to highlight what long lasting connection with products ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…It is these three levels that the authors of this research constitute the cognitive and affective systems in different measures. Aftab and Rusli (2017) are consistent with the abstraction hierarchy described by Norman (2004) through evaluation experiments in the used furniture design. Most participants are emotionally linked to the usability (behavioral level) and appearance (visceral level) of the evaluated furniture.…”
Section: The "Cognitive and Affective Systems" Should Be Integrated Into A Single Process In Product Evaluationssupporting
confidence: 88%
“…It is these three levels that the authors of this research constitute the cognitive and affective systems in different measures. Aftab and Rusli (2017) are consistent with the abstraction hierarchy described by Norman (2004) through evaluation experiments in the used furniture design. Most participants are emotionally linked to the usability (behavioral level) and appearance (visceral level) of the evaluated furniture.…”
Section: The "Cognitive and Affective Systems" Should Be Integrated Into A Single Process In Product Evaluationssupporting
confidence: 88%
“…Aftab et al [4] argue that this level produces long-term effects related to emotions, ownership satisfaction and exhibition of a certain product. Emotional attachment is determined by the user's disposition to perceive, reflect, and give a meaning to a product and not by the product itself.…”
Section: Reflective Levelmentioning
confidence: 99%
“…Over the last years, the way in which products are designed, developed and manufactured has been changing. The rapid advancement of technology generates an increasingly competitive and saturated market, providing users more choices based on what these products mean for themselves, how they can influence the user's life and how the user thinks, feels and acts [3][4][5]. Therefore, this requires mass manufacturing of products that cover each user's needs, endorsing a rising interest and eagerness for also designing the user experience [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, designing for an emotional connection is difficult, with designers finding effective simulation of product-attachment particularly challenging due to the end-user adding meaning and consequently value to a product and therefore not something which can be added prior to this (Mugge, 2007). A study by Aftab and Rusli (2017) ascertained that people's emotional attachment to products resulted in the products not being discarded. It concluded that users were most likely to keep broken furniture beyond its usefulness if they had an emotional story assigned to the memory of the furniture.…”
Section: The Role Of Designmentioning
confidence: 99%